Marketing Products With Wildlife: How to Make It Benefit Conservation - Braczkowski, Alexander; Allan, James R.; Jones, Kendall R.; Natali, Meganne; Biggs, Duan; Maron, Martine (Frontiers in Conservation Science, 2021)
• A key obstacle to wildlife conservation is a scarcity of funding. A recent piece by Courchamp et al. (2018) illustrates how for-profit businesses’ widespread use of threatened wildlife imagery could create complacency in the public about their conservation. • A “wildlife imagery royalty”, whereby businesses’, that use threatened wildlife in their marketing pay a small percentage of their sales to those species conservation could be revolutionary for conservation funding. However, businesses are not currently compelled to support the protection of the species espoused in their products. • We build upon the arguments presented by recent publications (Good et al. 2017 and Courchamp et al. 2018) for explore limitations and a number of key pathways that may help bring a wildlife imagery royalty to fruition.